GKT137831 and hydrogen peroxide increase the release of 6-nitrodopamine from the human umbilical artery, rat-isolated right atrium, and rat-isolated vas deferens - Britto-Júnior, José; Furlaneto, Rafael; Lima, Antonio Tiago; de Oliveira, Mariana Gonçalves; Severino, Beatrice; Frecentese, Francesco; Fiorino, Ferdinando; Caliendo, Giuseppe; Muscará, Marcelo Nicolás; De Nucci, Gilberto (Frontiers in Pharmacology, 2024)
Human umbilical artery (HUA), rat isolated right atrium and rat isolated vas deferens present basal release of 6-nitrodopamine (6-ND). The basal release of 6-ND from these tissues is significantly decreased (but not abolished) when the tissues were pre-incubated with L-NAME. Here, it was investigated the effect of pharmacological modulation of the redox environment on the basal release of 6-ND. The basal release of 6-ND was measured by LC-MS/MS. Pre-incubation (30min) of the tissues with GKT137831 (1M) caused significantly increase in the basal release of 6-ND from all tissues. In HUA, pre-incubation with diphenyleneiodonium (100M) also caused significant increases of the basal release 6-ND. Pre-incubation of HUA with H2O2 (100M) increased 6-ND basal release whereas pre-incubation with catalase (1000U/mL) significantly decreased it. Pre-incubation of HUA with SOD (250U/ml; 30min) also significantly increased the basal release of 6-ND. Pre-incubation of HUA with either allopurinol (100M) or uric acid (1mM) had no effect on the basal release of 6-ND. Pre-treatment of the HUA with L-NAME (100M) prevented the increase in the basal release of 6-ND induced by GKT137831, diphenyleneiodonium and H2O2. The results obtained indicate a major role for endogenous H2O2 and peroxidases as modulators of 6-ND biosynthesis/release and lack of peroxynitrite contribution.